Growth hormone positive effects on craniofacial complex in Turner syndrome. (November 2016) - Juloski, Jovana; Dumančić, Jelena; Šćepan, Ivana; Lauc, Tomislav; Milašin, Jelena; Kaić, Zvonimir; Dumić, Miroslav; Babić, Marko
Highlights: Long-term GH therapy has positive influence on craniofacial development in TS. Mandibular ramus and posterior face height are especially responsive. Development of acromegalic features is not a concern. Effects of GH therapy do not overcome craniofacial characteristics related to TS. Abstract: Objective: Turner syndrome occurs in phenotypic females with complete or partial absence of X chromosome. The leading symptom is short stature, while numerous but mild stigmata manifest in the craniofacial region. These patients are commonly treated with growth hormone to improve their final height. The aim of this study was to assess the influence of long-term growth hormone therapy on craniofacial morphology in Turner syndrome patients. Design: In this cross-sectional study cephalometric analysis was performed on 13 lateral cephalograms of patients with 45, X karyotype and the average age of 17.3 years, who have received growth hormone for at least two years. The control group consisted of 13 Turner syndrome patients naive to growth hormone treatment, matched to study group by age and karyotype. Sixteen linear and angular measurements were obtained from standard lateral cephalograms. Standard deviation scores were calculated in order to evaluate influence of growth hormone therapy on craniofacial components. Results: In Turner syndrome patients treated with growth hormone most of linear measurements were significantly larger compared to untreated patients. Growth hormone therapy mainly influenced posterior face height, mandibular ramus height, total mandibular length, anterior face height and maxillary length. While the increase in linear measurements was evident, angular measurements and facial height ratio did not show statistically significant difference. Acromegalic features were not found. Conclusions: Long-term growth hormone therapy has positive influence on craniofacial development in Turner syndrome patients, with the greatest impact on posterior facial height and mandibular ramus. However, it could not compensate X chromosome deficiency and normalize craniofacial features.